A new species of the genus Adpiasus Carvalho & Schaffner, 1973 (Insecta, Heteroptera, Miridae, Mirini) from French Guyana - Chérot, Frédéric (2014)
The authors describe Adpiasus riegeri sp. nov. (Insecta, Heteroptera, Miridae, Mirini), a new species of the genus from French Guyana. It is compared with the three existing species of the genus Adpiasus Carvalo & Schaffner, 1973, A. punctatus Carvalho & Schaffner, 1973, and A. mayanus Carvalho & Schaffner, 1973 from Mexico, as well as A. ecuadorianus Carvalho & Carpintero, 1986 from Ecuador. The characteristic features of the new species are described in detail and illustrated by photographs. Adpiasus mayanus is recorded for the first time from French Guyana.